Single-cell transcriptome and metagenome profiling reveals the genetic basis of rumen functions and convergent developmental patterns in ruminants - Deng, Juan; Liu, Ya-Jing; Wei, Wen-Tian; Huang, Qi-Xuan; Zhao, Li-Ping; Luo, Ling-Yun; Zhu, Qi; Zhang, Lin; Chen, Yuan; Ren, Yan-Ling; Jia, Shan-Gang; Lin, Yu-Luan; et al. (Genome Research, 2023)
The rumen undergoes developmental changes during maturation. To characterize this understudied dynamic process, we profiled single-cell transcriptomes of about 308,000 cells from the rumen tissues of sheep and goats at 17 time points. We built comprehensive transcriptome and metagenome atlases from early embryonic to rumination stages, and recapitulated histomorphometric and transcriptional features of the rumen, revealing key transitional signatures associated with the development of ruminal cells, microbiota, and core transcriptional regulatory networks. In addition, we identified and validated potential cross-talk between host cells and microbiomes and revealed their roles in modulating the spatiotemporal expression of key genes in ruminal cells. Cross-species analyses revealed convergent developmental patterns of cellular heterogeneity, gene expression, and cell–cell and microbiome–cell interactions. Finally, we uncovered how the interactions can act upon the symbiotic rumen system to modify the processes of fermentation, fiber digestion, and immune defense. These results significantly enhance understanding of the genetic basis of the unique roles of rumen.
10.1101/gr.278239.123